Effect of training on nursing professionals' knowledge about subcutaneous administration of enoxaparin (Research, Society and Development, 2025)
Blood extravasation resulting from venous trauma during subcutaneous administration of heparin can lead to complications such as pain and bruising. A recent meta-analysis indicates that slow injection (30s) of enoxaparin, compared to rapid injection (10s), is associated with reduced intensity and duration of pain, as well as lower occurrence and size of bruises after 48 to 72 hours. However, it is necessary to consider the knowledge about the applicability of the technique, as administering less than 1mL in 30 seconds is complex. The aim of the present research was to evaluate the pre- and post-intervention knowledge of nursing professionals regarding the administration of subcutaneous enoxaparin sodium injection. A quasi-experimental study was conducted in the postoperative ICU of a cardiac surgery hospital in São Paulo-SP. Included were nursing professionals, both nurses and active technicians. A semi-structured form containing 10 multiple-choice questions was applied in the pre- and post-intervention phases, and the impact assessment included direct observation, immediate feedback, and questionnaires filled out by participants before and after the intervention. The evaluation of knowledge level during the training was conducted descriptively, presenting results in frequency and percentage, as well as other statistical measures. Despite limitations such as the absence of long-term evaluation and the study being conducted in a single hospital, the findings reinforce the relevance of continuous investment in health education to reduce errors and promote patient safety.